Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/846782
|View full text |Cite
|
Sign up to set email alerts
|

Role of Genetic Alterations in the NLRP3 and CARD8 Genes in Health and Disease

Abstract: The complexity of a common inflammatory disease is influenced by multiple genetic and environmental factors contributing to the susceptibility of disease. Studies have reported that these exogenous and endogenous components may perturb the balance of innate immune response by activating the NLRP3 inflammasome. The multimeric NLRP3 complex results in the caspase-1 activation and the release of potent inflammatory cytokines, like IL-1β. Several studies have been performed on the association of the genetic altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 101 publications
1
47
0
3
Order By: Relevance
“…Although IL‐17 production can be regulated by NLRP3 activation, TNF production is mainly thought to occur through signals that lead to activation of nuclear factor kappa B . NLRP3 activation may amplify this production in an autocrine or paracrine fashion by inducing the maturation and release of IL‐1β and IL‐18, which then interact with their own membrane receptors . Furthermore, both cytokines have been involved in creating an autoinflammatory loop that characterizes these disorders, whereas IL‐17 is an important contributor for tissue recruitment of neutrophils, a central feature found in livers of mice with constitutive active NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL‐17 production can be regulated by NLRP3 activation, TNF production is mainly thought to occur through signals that lead to activation of nuclear factor kappa B . NLRP3 activation may amplify this production in an autocrine or paracrine fashion by inducing the maturation and release of IL‐1β and IL‐18, which then interact with their own membrane receptors . Furthermore, both cytokines have been involved in creating an autoinflammatory loop that characterizes these disorders, whereas IL‐17 is an important contributor for tissue recruitment of neutrophils, a central feature found in livers of mice with constitutive active NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms are suggested to be associated with the basal levels of IL‐1β and IL‐18. The G allele in rs10754558 was shown to enhance NLRP3 mRNA stability, leading to increased IL‐1 and IL‐18 secretion (Paramel, Sirsjo, & Fransen, ; Verma et al, ). Moreover, functional analysis has demonstrated that the mutant alleles of rs10754558 and rs4612666 could lead to the increment of the NLRP3 mRNA stability and enhanced the NLRP3 expression (Hitomi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these autoactivating NLRP3 mutations associated with CAPS, single nucleotide polymorphisms in NLRP3 have been associated with increased caspase‐1 activity in common diseases, such as Crohn's disease, rheumatoid arthritis, ankylosing spondylitis, and celiac disease . The importance of NLRP3 inflammasome‐mediated activation of IL‐1β and IL‐18 in the pathogenesis of common diseases has largely been validated in preclinical models, including models of Alzheimer's disease, acute graft‐versus‐host‐disease, multiple sclerosis, liver inflammation and fibrosis, gout, obesity and type 2 diabetes, and cardiovascular disease (e.g., atherosclerosis) .…”
Section: Nlrp3 In Health and Diseasementioning
confidence: 99%